[OP.2A.09] SYSTOLIC BLOOD PRESSURE VARIATION DURING 6 YEARS AND MORTALITY: THE AGE AMPLIFIES THE IMPACT OF A SPONTANEOUS INCREASE OR REDUCTION OF PRESSURE AMONG HYPERTENSIVE. (September 2016) - Thomas-Jean, F.; Pannier, B.; Hanon, O.; Czernichow, S.; Lemogne, C.; Simon, T.; Simon, J.; Danchin, N.
Abstract : Objective: A positive or negative variation blood pressure (BP) is associated with an increased mortality risk among hypertensive but not among normotensives (J Hum Hypertension, 2015). The arterial stiffness being increased by the age and high arterial BP, this relation between variation SBP and mortality was studied in 3 age groups, in both populations. Design and method: 83288 subjects, including 60199 normotensives and 23089 hypertensives (Systolic BP > = 140 mmHg or Diastolic > = 90 mmHg or antihypertensive treatment), aged from 18 to 95 years, who had at least 2 standard health check-up at the IPC Center (Paris) between 1992 and 2011 [average time between two visits (V1, V2): 5.9 ± 2.5 years]. SBP was measured after 10 minutes rest with an electronic device. Average follow-up after V2 was 6.1 ± 3.2 years. During this period, 3019 subjects died. Absolute variation between V1 and V2 was analyzed using quartile of the distribution (Q) among hypertensives and normotensives in 3 age groups: <55, 55–64, > = 65 years, considering the second quartile (no variation) as the reference group. Risk of mortality was evaluated using COX regression model (Hazard Ratio, IC 95%) including age, gender, BMI, cholesterol, triglycerides, glycaemia, alcohol, tobacco consumption, physical activity, health status, educational and initial SBP level. Results: Among normotensives, SBP decrease (Q1) between the two visits is not associated with all-cause mortality. However, increase of SBP (Q4) was associated with an excess of mortality among subjects < 55 years old (HR: 1.71 [1.16–2.51], p < 0.007). Among hypertensives, SBP decrease was associated with an excess of mortality after >65 years old (1.94 [1.10–3.44], p < 0.02), whereas increase in SBP (Q3, Q4) was associated with an increased risk of mortality from 55 years old (3.32 [1.62–6.82], p < 0.01), and 2.23 [1.24–3.98], p < 0.007, for Q4 among subjects > = 65 years. Conclusions: Among hypertensives, increase or decrease of SBP is deleterious among oldest subjects, suggesting a bad tolerance of BP variation during a very long time in a cardiovascular system less compliant to parietal constraints exposition. Among normotensives, increase SBP has a deleterious effect only among subjects before 55 years old, suggesting few effects of large arteries hemodynamic.